Comparison hybrid techniques-based mixed transform using compression and quality metrics - Zainab Ibrahim Abood Al-Rifaee; Samir Ibrahim Abood; Tarik Zeyad Ismaeel (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Image quality plays a vital role in improving and assessing image compression performance. Image compression represents big image data to a new image with a smaller size suitable for storage and transmission. This paper aims to evaluate the implementation of the hybrid techniques-based tensor product mixed transform. Compression and quality metrics such as compression-ratio (CR), rate-distortion (RD), peak signal-to-noise ratio (PSNR), and Structural Content (SC) are utilized for evaluating the hybrid techniques. Then, a comparison between techniques is achieved according to these metrics to estimate the best technique. The main contribution is to improve the hybrid techniques. The proposed hybrid techniques are consisting of discrete wavelet transform (W), multi-wavelet transform (M), and tensor product mixed transform (T) as 1-level W, M, and T techniques. WT and MT are the 2-level techniques, while WWT, WMT, MWT, and MMT are the 3-level techniques. For each level of each technique, a reconstructed process is applied. The simulation results using MATLAB 2019a indicated that the MMT is the best technique with CR=1024, R(D)=4.154, and PSNR=81.9085. Also, it is faster than the other techniques in the previous works as compared with them. Further research might investigate whether this technique can benefit image and speech recognition.